How to trigger mass market adoption of electric vehicles? Factors predicting interest in electric vehicles in Germany - Julius P. Wesche; Patrick Plötz; Elisabeth Dütschke (Fraunhofer-Institut für System- und Innovationsforschung ISI, 2016)
Plug-in electric vehicles (PPEVs) have noteworthy potential to reduce global and local emissions and are expected to become a relevant future market for vehicle sales. Both policy makers and car manufacturers have an interest to understand the future PEV user groups, also those beyond the current 'early adopter'. However, there are only a few empirical results available about potential future PEV users. Here, we use data from a representative survey on PEV interest from Germany to analyse factors that are related to interest in PEVs of private car buyers. Interest in PEV implies a positive attitude towards this new technology and is thus a prerequisite for later adoption. Our results show that technology affinity and the feeling that an PEV can serve the user's driving need are positively connected to interest in PEVs. Furthermore, persons that connect a strong feeling of independence with conventional vehicles are less likely to be interested in PEVs. Our results indicate that automakers promoting PEVs should focus their marketing on the new yet ready technology in the next years.
urn:nbn:de:0011-n-4259513
Keywords: 330; electric vehicles; early adopter; early majority; market diffusion; consumer behaviour